Validation of the 8th edition of the TNM staging system in 3,950 patients with surgically resected non-small cell lung cancer - Yun, Jae Kwang; Lee, Geun Dong; Kim, Hyeong Ryul; Kim, Yong-Hee; Kim, Dong Kwan; Park, Seung-Il; Choi, Sehoon (Journal of Thoracic Disease, 2019)
Background: The International Association for the Study of Lung Cancer introduced the 8th edition of the tumor, node, and metastasis (TNM) staging system for lung cancer. In this study, we validated the 8th edition of the TNM staging system and compared its discrimination power with that of the previous 7th edition. Methods: A retrospective analysis was carried out on patients who underwent complete resection with systematic lymph node dissection for non-small cell lung cancer (NSCLC) between 2006 and 2015 at a tertiary referral center in Seoul, South Korea. Cox regression model was used to identify significant differences between adjacent TNM stage groupings. The Concordance index (C-index), Akaike Information Criterion (AIC), and R2 measure were utilized to evaluate the discrimination ability of the staging systems. Results: A total of 3,950 patients (2,440 male, median age: 63 years) were analyzed. Median follow-up was 59 months (interquartile ranges, 38–88 months). According to the 8th edition, survival curves of overall survival (OS) and recurrence-free survival (RFS) within adjacent stage groupings showed significant differences except for IIA vs. IIB. Compared with the 7th edition, the 8th edition showed higher C-index (0.753 vs. 0.751), lower AIC (17,517 vs. 17,543), and higher R2 (0.178 vs. 0.171) values, indicating better discrimination ability. Conclusions: Stratification based on the 8th edition of the TNM staging system showed favorable prognostic validity compared with the 7th edition. The 8th edition also had superior discrimination ability in terms of OS and RFS.